THE TRADITON OF PALEMBANG WEDDING AS A SOURCE OF HISTORY LEARNING: Nilai Tradisi Pernikahan Adat Palembang Sebagai Sumber Belajar Sejarah di SMA - Kiki Ardilah; Dina sri nindiati; Kabib Sholeh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the historical values, cultural meanings, and educational significance embedded in the Palembang traditional marriage ceremony, as well as its relevance as an authentic history learning resource at the senior high school level. The study employed a qualitative descriptive method using a case study approach. Data were collected through observations conducted at SMAN 3 Palembang and the Sultan Mahmud Badaruddin II Museum, in-depth interviews with traditional leaders, customary authorities, cultural practitioners, and history teachers, as well as document analysis. The findings reveal that the Palembang traditional marriage ceremony preserves authentic historical traces inherited from the era of the Sriwijaya Kingdom and later refined during the reign of Sultan Mahmud Badaruddin II of the Palembang Sultanate. The ceremony embodies noble values, including mutual respect, deliberation, commitment, responsibility, sincerity, and family unity. As a living cultural heritage, this tradition serves as an effective history learning resource by connecting the past with the present, enabling students to gain a deeper understanding of local history while fostering historical awareness, cultural pride, and positive character development. It can be concluded that integrating the Palembang traditional marriage ceremony into history education significantly enhances students' understanding of local history and strengthens their cultural identity within the framework of the Merdeka Curriculum.